Evaluation of prolonged pain in preterm infants with pneumothorax using heart rate variability analysis and EDIN (Échelle Douleur Inconfort Nouveau-Né, neonatal pain and discomfort scale) scores - Mehmet Buyuktiryaki; Nurdan Uras; Nilufer Okur; Mehmet Yekta Oncel; Gulsum Kadioglu Simsek; Sehribanu Ozluer Isik; Serife Suna Oguz (Korean Pediatric Society, 2018)
Purpose The EDIN scale (Échelle Douleur Inconfort Nouveau-Né, neonatal pain and discomfort scale) and heart rate variability has been used for the evaluation of prolonged pain. The aim of our study was to assess the value of the newborn infant parasympathetic evaluation (NIPE) index and EDIN scale for the evaluation of prolonged pain in preterm infants with chest tube placement due to pneumothorax. Methods This prospective observational study assessed prolonged pain in preterm infants with a gestational age between 33 and 35 weeks undergoing installation of chest tubes. Prolonged pain was assessed using the EDIN scale and NIPE index. Results There was a significant correlation between the EDIN scale and NIPE index (r=-0.590, P=0.003). Prolonged pain is significantly more severe in the first 6 hours following chest tube installation (NIPE index: 60 [50-86] vs. 68 [45-89], P<0.002; EDIN score: 8 [7-11] vs. 6 [4-8], P<0.001). Conclusion Prolonged pain can be accurately assessed with the EDIN scale and NIPE index. However, evaluation with the EDIN scale is time-consuming. The NIPE index can provide instantaneous assessment of prolonged and continuous pain.